Dualisme Antara Hak Asasi Manusia Dan Kepentingan Publik Dalam Hal Menggunakan Masker Di Era Pandemi Covid 19 (Tinjauan Sosiologi Hukum) - Wijaya, Hanna; Haryanto, Imam (Lex Librum : Jurnal Ilmu Hukum, 2023)
Abstract The appearance of Covid-19, later on, a pandemic, stunned the world. The spread is very fast, and research continues today, making the WHO and government regulations that are still evolving. Implementing hygiene precautions such as using masks, washing hands with soap, bringing hand sanitisers, and preserving distance, generally called social distancing and independent isolation can be achieved by the group in breaking the chain of COVID-19 disease transmission. This analysis uses a research approach that reviews normative legal studies. In Indonesia, enforcing health protocols, including wearing masks, is still very difficult, the Indonesian people are not yet aware of breaking the Covid-19 spread chain. The use of shows and COVID-19 disease is correlated with human rights, and the public interest must be considered. Using a mask is everyone's fundamental right to breathe safe, virus-free air. Also, a mask honours collective interests rather than personal interests. Therefore, the government takes action by making legislation restricting the use of masks and enforcing other health protocols in this COVID-19 pandemic period, using sanctions to make citizens aware of the value of wearing masks today. Keywords: Human Rights; Public Interest; Law Applicable; Covid-19